The Influence of Transformational Leadership with the Mediating Role of Work Engagement and Job Satisfaction on Employee Performance - Nur Apriani Dahliana; Abdul Haeba Ramli (CV. ULIL ALBAB CORP, 2026)
In the context of globalization, which demands government apparatus to improve efficiency and the quality of public services, employee performance becomes a crucial factor for organizational success. This study aims to analyze the effect of transformational leadership on employee performance with the mediating roles of work engagement and job satisfaction among employees of the Tangerang Regency Government. A quantitative approach with an empirical study design was employed, involving 140 respondents selected through purposive sampling. Hypothesis testing was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that transformational leadership has a significant positive effect on work engagement, job satisfaction, and employee performance, both directly and indirectly through the mediating variables. These findings emphasize the importance of optimizing transformational leadership practices through clear communication of the organizational vision, consistent performance appreciation, and the creation of a supportive work environment to enhance employee engagement and job satisfaction. This research contributes to strengthening empirical evidence on the relationship between transformational leadership and employee performance in the public sector, while offering applicable and sustainable managerial strategies.